2006
DOI: 10.1002/chem.200600629
|View full text |Cite
|
Sign up to set email alerts
|

Antibiotic Resistance: Mono‐ and Dinuclear Zinc Complexes as Metallo‐β‐Lactamase Mimics

Abstract: Biomimetic systems containing one or two zinc(II) ions supported by phenolate ligands were developed as functional mimics of metallo-beta-lactamase. These complexes were shown to catalytically hydrolyze beta-lactam substrates, such as oxacillin and penicillin G. The dinuclear zinc complex 1, which has a coordinated water molecule, exhibits high beta-lactamase activity, whereas the dinuclear zinc complex 2, which has no water molecules, but labile chloride ligands, shows a much lower activity. The high beta-lac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
44
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 42 publications
(47 citation statements)
references
References 51 publications
3
44
0
Order By: Relevance
“…The steric and electronic nature of this aminophenolate ligand can readily be changed to fine tune the property of its complex, which is often used as a catalyst for reactions such as ring-opening metathesis polymerization of 2-norbornene [2], lactide polymerization [3] and the hydrolysis of b-lactam substrates [4]. van Koten and co-workers reported vanadium complexes of 1 which are catalysts for the polymerization of a-olefins [5].…”
Section: N N Ohmentioning
confidence: 98%
“…The steric and electronic nature of this aminophenolate ligand can readily be changed to fine tune the property of its complex, which is often used as a catalyst for reactions such as ring-opening metathesis polymerization of 2-norbornene [2], lactide polymerization [3] and the hydrolysis of b-lactam substrates [4]. van Koten and co-workers reported vanadium complexes of 1 which are catalysts for the polymerization of a-olefins [5].…”
Section: N N Ohmentioning
confidence: 98%
“…31,90,112 Numerous research groups have reported Zn(II)Zn(II) hydrolase mimics. [14][15][16]18,20,22,90,92,101,[122][123][124][125][126][127] Bringing two Zn(II) ions in 132 The bidentate-bridging binding mode of the diphenyl phosphate was also proposed in solution using 31 P-NMR measurements because of the rather large shifts observed for the phosphate ester signal. 132 The separation of the two zinc centres in the biomimetics has been shown to be important.…”
Section: Dinuclear Zinc Hydrolase Mimicsmentioning
confidence: 99%
“…Amino acid residues involved in the active site of the NDM-2 were found to be: (Figure 3). Metallo-β-lactamases are generally characterized by presence of catalytic water molecules within the active site which are required for enzyme catalytic activity (Tamilselvi, Nethaji, & Mugesh, 2006;Wommer et al, 2002). Results showed the presence of six water molecules at molecule number 531, 538, 540, 562, 573 and 591 associated with the active site of NDM-2.…”
Section: Resultsmentioning
confidence: 99%